Aprendizagem da docência em experiências de educação a distância: implicações para a prática docente presencial - Martins, Selma Leila Bergo (Universidade Federal de São Carlos, 2015)
This masters dissertation was developed with the aim of analyze how the learning of teaching for Distance Education occurs, through the continuous formation and the teaching performance on Distance Education and the implications that this knowledges bring to the presential teaching practices. As Distance Education is growing and being implemented in a lot of Brazilian s universities, we would like to know how the teaching formation to this modality is being learned and how this learning is being used on Presential Education. Understand this dynamic is relevant to the distant and presential teaching formation, however, is still a poorly researched subject, reason why this research was conducted. To make the realization of this study and establish the theoretical referentials, it was needed to characterize the Distance Education model, adopted by Higher Education Institutions chosen for carrying out this research, as well characterize the virtual teaching and the presential teaching. Furthermore, we treat of the teaching competence for the use of technologies and, lastly, we seek to identify the main presential teaching practices that were changed according to the Distance Education experience. Thus, the methodology used was the quantitative and qualitative approach, developed through the sending of an e-mail to the Distance Education coordinators of 11 universities, that is, 10% of the universe of the Universities that belong to UAB system, containing a request that the coordinators resend the survey questionnaire to their teachers so we could collect the datas. In total, returned 233 questionnaires for analysis and data interpretation. Of these, we selected four Institutions that participated the most, being three federals and one statewide. All of this collected material a rich source to clarify how are learned the knowledge on virtual teaching and how this knowledge implies on presential teaching. As main results of our research, can be mentioned: the use of a large number of technological tools in the presential classes; the accomplishment of more teamwork, less expository classes and the use of more dynamic methodologies and interactives, increase of the communication canals and diversification of the evaluations forms.
Learning of teaching in distance education experiences and implication for presential teaching practice
Keywords: Aprendizagem profissional da docência; Docência virtual; Educação a distância; Prática docente; CIENCIAS HUMANAS::EDUCACAO